Baseline White Matter Hyperintensities and Hippocampal Volume are Associated With Conversion From Normal Cognition to Mild Cognitive Impairment in the Framingham Offspring Study. (January 2018) - Bangen, Katherine J.; Preis, Sarah R.; Delano-Wood, Lisa; Wolf, Philip A.; Libon, David J.; Bondi, Mark W.; Au, Rhoda; DeCarli, Charles; Brickman, Adam M.
Abstract : Introduction: We examined associations between magnetic resonance imaging (MRI) markers of cerebrovascular disease and neurodegeneration with mild cognitive impairment (MCI) diagnosis at baseline and conversion from normal cognition to MCI at follow-up. Methods: Framingham Offspring participants underwent brain MRI and neuropsychological assessment at baseline (n=1049) and follow-up (n=561). Participants were classified at baseline and at follow-up as cognitively normal or MCI using sensitive neuropsychological criteria. White matter hyperintensity (WMH) volume, covert brain infarcts, hippocampal volume, and total cerebral brain volume were quantified. Results: Baseline measures of WMH and hippocampal volume were associated with MCI status cross-sectionally and also with conversion from normal cognition to MCI at 6.5-year follow-up. Annualized change rates in total cerebral brain volume and hippocampal volume were associated with conversion from normal cognition to MCI to follow-up. Discussion: Baseline WMH and hippocampal volume are markers that are both associated with conversion from normal cognition to MCI, highlighting the role of both vascular lesions and neurodegeneration in MCI. Abstract : Supplemental Digital Content is available in the text.